Leptin and Other Factors as Determinants of Insulin Secretion and Sensitivity in Bangladeshi Type 2 Diabetic Subjects - Roy, Manindra Nath; Akter, Salima; Jafarulla, Mohammad; Mollah, Forhadul Hoque; Saha, Ajanta Rani; Ali, Liaquat (Journal of Bangladesh Society of Physiologist, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: The relative contribution of insulin secretion and sensitivity in the development of Type 2 diabetes mellitus (T2DM) vary from population to population due to the heterogeneous nature of the disease. The study was undertaken to evaluate insulin secretory capacity and sensitivity in a Bangladeshi Type 2 diabetic population and to explore the association of some of the anthropometric and biochemical factors known to modulate B-cell function and insulin action. Methods: Ninety one T2DM subjects and 32 age-matched controls were studied for their fasting plasma glucose (FPG), lipids, HbA1c (by HPLC), leptin and C-peptide (ELISA). Insulin secretion (HOMA B) and insulin sensitivity (HOMA S) were calculated by homeostasis model assessment (HOMA). Results: Both insulin secretion and sensitivity were significantly reduced in diabetic as compared to control (HOMA B%, geometric meanÂ±SD, 35.65Â±1.75 vs. 96.29Â±1.50, p < 0.001; HOMA S%, 68.66Â±1.71 vs. 104.951.63, p < 0.001). However, B-cell dysfunction was predominant than insulin resistance in predicting T2DM as the discriminate function coefficient for HOMA B (1.098) was greater than that for HOMA S (0.821). In T2DM, HOMA B had positive correlation with BMI (r=0.368, p < 0.001) and HOMA S was inversely correlated to BMI (r=-0.261, p < 0.01), WHR (r=-0.258, p < 0.01) and plasma TG (r=-0.233, p < 0.001). On multiple regression analysis HOMA B and HOMA S were found to be inversely associated to FPG (p < 0.001) and leptin (p < 0.05) in T2DM. Conclusions: Both insulin secretory dysfunction and insulin resistance are present in Bangladeshi T2DM subjects, but B-cell failure seems to be the predominant abnormality. BMI, plasma glucose, insulin and leptin are the major determinants of insulin secretory capacity and generalized as well as central obesity, plasma glucose, triglycerides, insulin and leptin are among the major determinants of insulin sensitivity in this population. Key Words: Leptin, Insulin, Diabetes Â doi: 10.3329/jbsp.v3i0.1786 J Bangladesh Soc Physiol. 2008 Dec;(3):1-7.